Lectures on crystal field theory, delivered at the Summer School in Ligand Field Theory, 1970, Bangalore - Judd, Brian R. (Lectures on mathematics and physics. Physics, 1972)
On an aspect of mathematical physics employing crystallography for measuring ions.